Carbon sequestration rate in sediment mangroves from natural and rehabilitated mangroves - D. Ariyanto; D. Pringgenies (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: A major function of mangroves is carbon sequestration in sediment. This study aimed to determine differences in carbon content in sediments in various types of mangroves and environmental parameters.METHODS: This study was carried out in Pesawaran as a natural mangrove and in South Lampung as rehabilitated mangrove in Indonesia. Purposive sampling method was used by considering the types of mangroves at the locations. Sediment sampling was taken using a polyvinyl chloride pipe with a diameter of 47.46 milimeters and a height of 30 centimeters. The sediment parameters measured were bulk density, carbon stock, and sequestration. Environmental parameters measured included sediment texture, potential of hydrogen, temperature, salinity, and total dissolved solids. A statistical analysis was conducted using the principal component analysis to determine the relationship between the organic carbon stock and the environmental parameters.FINDINGS: The study results showed that natural mangroves (Pesawaran) had a higher organic carbon value at 2.2 ± 0.32 percent than rehabilitated mangroves (South Lampung) at 0.9 ± 0.25 percent. The principal component analysis results revealed that organic carbon, carbon dioxide equivalent, carbon stock, and carbon sequestration had positive correlation characteristics influenced by salinity, silt, and clay, while negative correlation characteristics were affected by temperature, total dissolved solids, and sand. The distribution of sediment texture tended to show more silt in rehabilitated mangroves, while natural mangroves tended to have the same composition between sand and silt. The potential of hydrogen conditions in natural and rehabilitated mangroves showed no significant differences in values. The salinity in Pesawaran, which was classified as a natural mangrove, was higher due to the influence of the tides and was directly facing the shoreline. Meanwhile, in South Lampung, which was categorized as a rehabilitated mangrove, the salinity was lower due to the long dry season and the canals being unable to support the water entering the mangroves.CONCLUSION: The organic carbon content at the research locations was influenced by the older age of the Rhizophora stylosa compared to that of the Rhizophora mucronata and Ceriop tagal types of mangroves. The carbon sequestration rate values showed 1.65–3.14 for natural mangroves and 0.29–1.25 for rehabilitated mangroves, thus establishing that the rate is higher (2–3 times) in natural mangroves than in rehabilitated mangroves.